BIMBINGAN KELOMPOK UNTUK MENINGKATKAN PENYESUAIAN SOSIAL SISWA KELAS IX-E SMP NEGERI 1 WONOASRI KABUPATEN MADIUN - NINIK SUHARTI (Universitas PGRI Madiun, 2014)
Changes that occur in the community often felt too fast .As a result, thereare people who are able to adjust and compensate for the change and some arenot able to adapt itself. For those who are not able to adapt to the changingdemands that will have problems in adjustment and social .In the process of socialadjustment , students are exposed to the demands and expectations of a verycomplex and difficult .Many students feel hesitant and less responsive to thesituation at hand .As a result of the difficulties to adapt themselves to theenvironment , eventually students perform actions that violate norms. Found a lotof students who perform inappropriate acts , violate school rules , late entry ,ditching , brawl , and others .Group counseling is expected to answer theseproblems .The results of observations in class IX - E SMP Negeri 1 Wonoasri foundsome students who have low levels of social adjustment in order to comply withthe school that impact on learning outcomes is low.This study uses action research ( Classroom action research ) to class IX -E SMP Negeri 1 Wonoasri with the aim to help students improve their ability inschool and social adjustment can adjust to social learning on a regular basis .From the results of this study concluded that group counseling canimprove the social adjustment of students effectively, Although there are somestudents who have not demonstrated a significant improvement or fall into thecategory of students who no change significantly and there are also students whoshowed a decline in understanding of themselves , this may be due to the problemsit faces more difficult than the problems faced by other friends or because there isno desire in him to improve social adjustment .